Pengaruh Layanan Mahasiswa Profesi Dokter Terhadap Tingkat Kepercayaan Pasien di Ruang Rawat Inap RS Ibnu Sina - Tallamma, Muhammad Alkautsar; Haeruddin, Haeruddin; Samsualam, Samsualam (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2023)
Background: The level of patient trust in the services of professional medical students is one of the most important things in improving quality health services. Aim: This study aims to analyze the relationship between the influence of professional medical student services on the patient's level of trust. This type of quantitative research with a cross sectional approach was conducted at the Ibnu Sina Hospital, Wakaf Foundation, Indonesian Muslim University. Method: A sample of 68 people were selected using accidental sampling. Data were obtained through the results of distributing questionnaires which were then analyzed using the Spearman correlation test. Results: Based on table 6.0 it is known that respondents with the influence of visits, prescriptions, infusions, drug administration, and examination control with each value (p = 0.000), the results of the analysis for this variable using chi square analysis obtained a value of p = 0.000 because the probability value α <0.05 then Ha is accepted which means there is a significant relationship. Conclusion: Services performed by medical students in the form of visits, prescription writing, infusion, medication administration, and control examinations, do not reduce the patient's level of trust.